APLIKASI KITOSAN SEBAGAI ANTIMIKROBA PADA CANGKANG KAPSUL BERBASIS KARAGENAN DARI RUMPUT LAUT Eucheuma cottonii - Muhammad Ryan (Inovasi Pembangunan : Jurnal Kelitbangan, 2022)
The capsule shell is one of the edible film applications in the pharmaceutical field. As a packaging material, the capsule shell must have antimicrobial properties in order to protect the material being wrapped against fungi and bacteria. In this study, a study was conducted on the effect of chitosan addition in the manufacture of hard capsule shells from carrageenan seaweed Eucheuma cottonii on antimicrobial properties. Carrageenan weight of 2 grams, Carboxymethyl Cellulose (CMC) 0.05 grams, and gelatinization temperature at 95oC with variations in the addition of chitosan, namely 0, 2, 4, 6, 8, 10%. From the variations that exist, the best capsule shells are found in the addition of chitosan by 10% with a moisture content value of 14.2%, disintegration time 13.35 minutes, a total plate value value of 9 x 103 cfu / ml, and a yeast mold value of 0.5.